Perilaku Komunikasi Mahasiswa Penggemar K-Pop di UIN Kiai Haji Achmad Siddiq Jember - Yulianti, Putri; Ardiansyah, Muhammad (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This research is motivated by the phenomenon of the Korean Pop (K-Pop) fever which is very loved and crazed among teenagers today, especially students of UIN K.H Achmad Siddiq in the city of Jember. The flow of globalization is a factor supporting the accelerated spread of Korean Pop culture. The absence of media control over this Korean wave makes K-Pop freely influence the values ​​of religious behavior and cultural identity of its fans. This study aims to determine how the form of communication behavior and want to know how religious behavior before and after UIN KHAS Jember students become K-Pop fans. The method used in this research is a qualitative research method with a descriptive research type with a phenomenological approach model. Meanwhile, the data collection technique was carried out by means of observation, interviews, and documentation. Data analysis techniques according to Miles and Huberman and for the validity of the data using triangulation techniques. The results of this study explain the closed and open communication behavior of K-Pop fan students. The behavior shown has led to the direct action and practice of the individual. Changes in religious behavior is that nothing has changed in terms of faith and worship because liking K-Pop and doing worship and a belief are two different things.